Constraints on perfect fluid and scalar field dark energy models from future redshift surveys - Amendola, Luca; Quercellini, Claudia; Giallongo, Emanuele (Arxiv, 2004)
We discuss the constraints that future photometric and spectroscopic redshift surveys can put on dark energy through the baryon oscillations of the power spectrum. We model the dark energy either with a perfect fluid or a scalar field and take into account the information contained in the linear growth function. We show that the growth function helps to break the degeneracy in the dark energy parameters and reduce the errors on $w_0,w_1$ roughly by 30% making more appealing multicolor surveys based on photometric redshifts. We find that a 200 square degrees spectroscopic survey reaching